A high-airtightness metal-resin composite and a metal surface nano-processing method thereof
By forming micro and nanopores on the surface of metal parts and fully adsorbing into the holes with thiourea-based modifications, the resin can be completely filled, and the problem of low airtightness of the metal resin composite in the prior art is solved, and a metal resin composite with high airtightness and higher waterproofness is achieved.
Patent Information
- Application Number
- CN201910488201.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-06-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2039-06-05
AI Technical Summary
The metal resin composites manufactured by existing nanoforming technology are not of high airtightness, which is difficult to meet the requirements of consumer electronic products such as smart watches and smartphones for higher waterproofing levels.
By forming micropores of 200-400um diameter on the surface of the metal component, and nanopores of 30-60nm diameter are formed on the inner side walls of the metal component by electrochemical oxidation treatment. The thiourea modifier is used as a coupling agent to fully adsorb in the holes during the electrochemical oxidation treatment, so that the resin can completely fill the holes, thereby improving the airtightness of the metal resin composite.
The metal resin composite with high airtightness is achieved, which improves its waterproofness and can meet the requirements of higher waterproofing grades.
Smart Images

Figure CN110091462B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano-molding, and in particular to a high-airtightness metal-resin composite and a metal surface nano-processing method thereof. Background Art
[0002] Nanomolding technology refers to the use of chemical corrosion technology to form numerous nanoscale micropores on the metal surface, and then forming a firm metal-resin composite through in-mold injection molding technology. Due to the advantages of good texture and high mechanical strength of metal appearance parts, most of the appearance parts of consumer electronic products such as smart phones and smart watches currently use metal appearance parts. However, since metal appearance parts have a shielding effect on electromagnetic waves, it is necessary to cut several independent metal edge strips on the metal appearance parts as antennas, and then use nanomolding technology to connect multiple independent metal parts into one, such as connecting the upper metal edge strip, the lower metal edge strip and the middle metal body of the smartphone shell into one, and connecting the upper metal shell and the lower metal shell of the smart watch into one. Existing nanomolding technology mainly focuses on the firmness of the combination of metal and resin. However, the high bonding strength between metal and resin is not directly related to high air tightness. This is because during injection molding, the resin and metal can be firmly combined into a whole through the "embedding" effect of numerous nano-micropores. Even if the resin does not completely fill the nano-micropores, it has limited effect on the firmness of the composite, but it will reduce the air tightness of the composite.
[0003] As smart watches, smart phones and other consumer electronic products have higher and higher requirements for waterproof level, the air tightness level of metal resin composites manufactured by ordinary nano molding technology is not high, and it is difficult to meet the higher requirements of waterproof level. In terms of nano molding technology, the main invention patents that have been authorized are the following two: Patent 1: Metal resin composite and its manufacturing method, patent number 201180056794.8, its metal surface treatment method is hereinafter referred to as "T treatment"; Patent 2: A plastic and metal composite material and its manufacturing method, patent number 201310231734.6, its metal surface treatment method is hereinafter referred to as "E treatment". T treatment uses an etching process to form 20-80nm nanopores on the surface of aluminum alloy, and adsorbs amine compounds on its surface to react chemically with plastic to form a stable connection; E treatment uses a combination of chemical corrosion and electrochemical technology to first form micron holes with a diameter of 100-300um on the metal surface, and then form a large number of nano holes with a diameter of 20-40nm on the inner side walls of these micron holes. After the nanopores are formed, the E treatment uses a weak alkaline solution to neutralize the acidic solution in the nanopores, and is immersed in a coupling agent that can react with PPS or PBT, so that the nanopores are filled with this coupling agent, which is used to chemically react with the plastic to form a stable connection.
[0004] Whether the metal-resin composite is manufactured by T-treatment or E-treatment nanomolding technology, its firmness can be guaranteed, but its airtightness level is not high, and it is difficult to meet the higher requirements of waterproof level. This is because, whether it is the amine compound of T-treatment or the coupling agent of E-treatment, they only form a "thin film" in the nanopores. During in-mold injection molding, although the resin can penetrate into the nanopores through the chemical reaction between the resin and this thin film, the resin and the metal are firmly combined into a whole through the "embedding" effect of numerous micropores, but the resin cannot completely fill the nanopores, resulting in the low airtightness level of the metal-resin composite. With the increasing requirements for waterproof level of consumer electronic products such as smart watches and smart phones, how to improve the airtightness of metal-resin composites manufactured by nanomolding technology has become a technical problem. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a high-airtightness metal-resin composite and a metal surface nano-treatment method thereof. Its main purpose is to solve the problem that the airtightness level of the metal-resin composite manufactured by the existing nano-molding technology is not high.
[0006] The technical solution adopted by the present invention is:
[0007] The present invention includes a high-airtightness metal-resin composite, which includes a metal component, a resin and a coupling agent. The metal component is treated with sand to form a large number of micron holes with a diameter of 200-400um on its surface, and a large number of nano holes with a diameter of 30-60nm are uniformly formed on the inner side wall of each micron hole through electrochemical oxidation treatment. Two metal components are connected to the resin through the coupling agent, and the coupling agent is a thiourea modifier. Under the action of the current in the electrochemical oxidation process, the thiourea modifier is filled in the micron holes and nano holes of the metal component, the resin is tightly combined with the thiourea modifier, and the metal component is also tightly combined with the thiourea modifier, so that the resin can be filled in the micron holes and nano holes of the metal component and combine the two metal components together.
[0008] In the above scheme, the resin serves as an intermediate connecting two metal parts, and the thiourea modifier is a coupling agent between the metal parts and the resin. Under the action of the electric current in the electrochemical oxidation treatment process, the thiourea modifier is completely filled in the micropores and nanopores of the metal parts; the thiourea modifier has two chemical bonds. During in-mold injection molding, one chemical bond can be tightly combined with the metal part, and the other chemical bond can be tightly combined with the resin, so that the resin can be completely filled in the micropores and nanopores of the metal part, and then the two pieces of metal are firmly combined together, thereby obtaining a highly airtight metal-resin composite, improving airtightness and waterproofness.
[0009] Furthermore, the material of the metal component is one of aluminum, aluminum alloy, magnesium alloy, copper alloy, titanium alloy or stainless steel.
[0010] In the above solution, there are many materials for the metal parts, so as to adapt to the metal shells of most smart electronic products on the market and improve the application scope of the present invention.
[0011] Furthermore, the metal component is a metal upper shell, a metal lower shell, a metal shell, or an independent side strip cut from the shell of the smart electronic product.
[0012] In the above scheme, since the metal appearance part has a shielding effect on electromagnetic waves, it is necessary to cut several independent metal edge strips on the metal appearance part as antennas. The metal part can be the metal of the shell itself or the cut metal edge strip. These relatively separate components can be connected together by resin.
[0013] Furthermore, the resin is one or more of PPS, PBT, PA, and PC resins, or a mixture of them with glass fiber, or a mixture of them with carbon fiber.
[0014] In the above scheme, there are many types of resins to choose from, and the resin has high versatility.
[0015] Furthermore, the thiourea modified product is a triazine thiourea modified product.
[0016] In the above scheme, the triazine thiourea modified product is a better coupling agent among the thiourea modified products and has excellent performance.
[0017] The present invention also includes a method for nano-processing the metal surface of a high-air-tightness metal-resin composite, which comprises the following steps:
[0018] Step 1: Clean the metal parts to remove grease on their surfaces;
[0019] Step 2: performing sand treatment on the metal component to form numerous micron-sized holes on its surface;
[0020] Step 3: performing dust removal treatment on the metal parts to preliminarily remove the gray film on the surface thereof;
[0021] Step 4: performing chemical polishing on the metal component to further remove the gray film on its surface;
[0022] Step 5: performing oxidation treatment on the metal component to uniformly form numerous nanoscale pores on the inner sidewalls of the microscale pores, and adding a thiourea modifier when the metal component is subjected to oxidation treatment, so that the thiourea modifier can be fully adsorbed in the microscale pores and nanoscale pores under the action of electric current;
[0023] Step 6: Wash the metal parts with water to remove the acidic substances remaining on the surface;
[0024] Step 7: Dry the metal parts to remove the residual water on the surface.
[0025] In the above scheme, 1. the electrochemical oxidation treatment and the adsorption of the thiourea modifier are arranged in the same process. Under the action of electric current, the thiourea modifier can be fully adsorbed in the micrometer-scale holes and nanometer-scale holes of the metal parts, which can avoid the problem that the existing technology cannot completely fill the micrometer-scale holes and nanometer-scale holes of the metal parts with the coupling agent; 2. The coupling agent between the metal and the resin adopts the thiourea modifier, which has two chemical bonds. During in-mold injection molding, one chemical bond can be tightly combined with the metal, and the other chemical bond can be tightly combined with the resin, so that the resin can be completely filled in the micrometer-scale holes and nanometer-scale holes of the metal parts, and the two pieces of metal are firmly combined together, thereby obtaining a metal-resin composite with high airtightness.
[0026] Furthermore, in step 2, the diameter of the micron-scale pores is controlled to be 200-400 um. In step 5, the diameter of the nano-scale pores is controlled to be 30-60 nm.
[0027] In the above scheme, the diameter of the micron-scale holes and nano-scale holes generated is experimentally controlled, and the data range is comprehensively obtained based on the adsorption force of the resin and coupling agent, as well as the difficulty of implementing the process.
[0028] Furthermore, the thiourea modified product is a triazine thiourea modified product.
[0029] In the above scheme, the triazine thiourea modified product is a better coupling agent among the thiourea modified products and has excellent performance.
[0030] Furthermore, the ash removal treatment is a chemical etching process, and the chemical polishing treatment is a chemical etching process using a phosphoric acid stock solution.
[0031] In the above scheme, the ash removal treatment adopts chemical corrosion, and the chemical polishing treatment adopts chemical corrosion of phosphoric acid solution. The combination of the two treatments has obvious effect and ensures that the ash film on the surface of the metal parts is completely removed. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the partially enlarged structure of the high airtightness metal-resin composite in the invention.
[0033] In the figure: 1-metal parts, 2-resin, 3-coupling agent. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present application more clear, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0035] Reference Figure 1 , shows a high-airtightness metal-resin composite in an embodiment, the high-airtightness metal-resin composite comprises a metal component 1, a resin 2 and a coupling agent 3, the metal component 1 is treated with sand to form a large number of micron holes with a diameter of 200-400um on its surface, and a large number of nano holes with a diameter of 30-60nm are uniformly formed on the inner side wall of each micron hole through electrochemical oxidation treatment, the two metal components 1 are connected to the resin 2 through the coupling agent 3, the coupling agent 3 is a thiourea modifier, under the action of the current in the electrochemical oxidation process, the thiourea modifier is filled in the micron holes and nano holes of the metal component 1, the resin 2 is tightly connected to the thiourea modifier, and the metal component 1 is also tightly connected to the thiourea modifier, so that the resin 2 can be filled in the micron holes and nano holes of the metal component 1 and combine the two metal components 1 together. The resin 2 serves as an intermediate connecting the two metal parts 1, and the thiourea modifier is a coupling agent 3 between the metal part 1 and the resin 2. Under the action of the electric current in the electrochemical oxidation treatment process, the thiourea modifier is completely filled in the micropores and nanopores of the metal part 1; the thiourea modifier has two chemical bonds. During in-mold injection molding, one chemical bond can be tightly combined with the metal part 1, and the other chemical bond can be tightly combined with the resin 2, so that the resin 2 can be completely filled in the micropores and nanopores of the metal part 1, and then the two pieces of metal are firmly combined together, thereby obtaining a metal-resin 2 composite with high airtightness.
[0036] The metal component 1 is made of one of aluminum, aluminum alloy, magnesium alloy, copper alloy, titanium alloy or stainless steel. The metal component 1 can be made of a variety of materials to adapt to the metal shells of most smart electronic products on the market, thereby increasing the application scope of the present invention.
[0037] The metal component 1 is a metal upper shell, a metal lower shell, a metal shell or an independent edge strip cut from the shell of the smart electronic product. Since the metal appearance part has a shielding effect on electromagnetic waves, it is necessary to cut several independent metal edge strips from the metal appearance part as antennas. The metal component 1 can be the metal of the shell itself or the cut metal edge strip. These relatively separate components can be connected together by resin 2.
[0038] The resin 2 is one or more of PPS, PBT, PA, and PC resins, or a mixture of these with glass fiber, or a mixture of these with carbon fiber. The resin 2 can be made of a variety of materials and has high versatility.
[0039] The thiourea modified product is a triazine thiourea modified product. The triazine thiourea modified product is a better coupling agent among the thiourea modified products and has excellent performance.
[0040] The present invention also includes a method for nano-processing the metal surface of a high-air-tightness metal-resin composite, which comprises the following steps:
[0041] Step 1, cleaning the metal parts to remove grease on their surfaces; the cleaning process adopts an ultrasonic degreasing process, the ratio of alkaline degreasing agent to water is controlled at 50g / L-80g / L, the water tank temperature is controlled at 55°C-65°C, and the degreasing time is controlled at 1 minute-3 minutes; the main components of the cleaning agent include non-ionic surfactants, anionic surfactants, sodium metasilicate pentahydrate and corrosion inhibitors.
[0042] Step 2: Performing sand treatment on the metal parts to form numerous micron-sized holes on their surfaces; the sand treatment is a strong acid chemical corrosion process, the sand temperature is controlled at 40°C-60°C, the ratio of sand solution to water is controlled at 350g / L-450g / L, and the immersion time is controlled at 20 seconds-60 seconds; the sand solution is a mixed aqueous solution of sulfuric acid and hydrochloric acid.
[0043] Step three, the metal parts are subjected to deashing treatment to preliminarily remove the gray film on the surface; the deashing treatment is a chemical corrosion process, the ratio of nitric acid to water is controlled at 150g / L-250g / L, the ratio of deashing agent to water is controlled at 80g / L-120g / L, the deashing temperature is controlled at 10℃-40℃, and the deashing time is controlled at 1 minute-3 minutes.
[0044] Step 4: Perform chemical polishing on the metal parts to further remove the gray film on the surface; the chemical polishing is a chemical corrosion process using phosphoric acid stock solution, the chemical polishing temperature is controlled at 85°C-95°C, and the chemical polishing time is controlled at 30 seconds-60 seconds.
[0045] Step 5, oxidizing the metal parts to uniformly form numerous nano-scale holes on the inner side walls of the micron-scale holes, adding thiourea modifiers when the metal parts are oxidized, so that the thiourea modifiers can be fully adsorbed in the micron-scale holes and nano-scale holes under the action of electric current; the oxidation treatment is an electrochemical treatment process, the ratio of phosphoric acid to water in the oxidizing solution is controlled at 250g / L-350g / L, the ratio of sulfuric acid to water is controlled at 60g / L-80g / L, the thiourea modifier is added to the oxidizing solution, the ratio of the thiourea modifier to the oxidizing solution is controlled at 10g-20g / L, the water tank temperature is controlled at 18°C-20°C, the oxidation time is controlled at 15 minutes-20 minutes, and the voltage is controlled at 18V-22V.
[0046] Step 6: Wash the metal parts with water to remove the acidic substances remaining on the surface; the water washing is carried out with pure water, and the water tank temperature is controlled at 10°C-40°C.
[0047] Step 7: Dry the metal parts to remove the residual moisture on the surface, and perform in-mold injection molding within 6 hours to avoid excessive volatilization of the thiourea modifier adsorbed in the micron-scale pores and nano-scale pores, so that the resin can completely fill the micron-scale pores and nano-scale pores of the metal parts during in-mold injection molding, thereby forming a metal-resin composite with high airtightness; the drying temperature of the drying treatment is controlled at 70°C-80°C, and the drying time is controlled at 8 minutes-12 minutes.
[0048] The above-mentioned metal surface nano-treatment method of a high-air-tightness metal-resin composite has the following beneficial effects: 1. The electrochemical oxidation treatment and the adsorption of the thiourea modifier are arranged in the same process. Under the action of the electric current, the thiourea modifier can be fully adsorbed in the micrometer-level holes and nanometer-level holes of the metal parts, which can avoid the problem that the coupling agent cannot completely fill the micrometer-level holes and nanometer-level holes of the metal parts in the prior art; 2. The coupling agent between the metal and the resin adopts the thiourea modifier, which has two chemical bonds. During in-mold injection molding, one chemical bond can be tightly combined with the metal, and the other chemical bond can be tightly combined with the resin, so that the resin can be completely filled in the micrometer-level holes and nanometer-level holes of the metal parts, and the two pieces of metal are firmly combined together, thereby obtaining a high-air-tightness metal-resin composite.
[0049] In step 2, the diameter of the micron-scale pores is controlled at 200-400um. In step 5, the diameter of the nano-scale pores is controlled at 30-60nm. The diameters of the micron-scale pores and nano-scale pores are controlled experimentally, and the data range is obtained comprehensively based on the adsorption force of the resin and coupling agent, as well as the difficulty of the process.
[0050] The thiourea modified product is a triazine thiourea modified product. The triazine thiourea modified product is a better coupling agent among the thiourea modified products and has excellent performance.
[0051] The above is a specific description of the preferred implementation of the present invention, but the present invention is not limited to the described embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A high airtightness metal-resin composite, characterized in that: It includes metal parts, resin and coupling agent. The metal parts are treated with sand to form numerous micron holes with a diameter of 200-400um on their surfaces. Electrochemical oxidation is used to uniformly form numerous nano holes with a diameter of 30-60nm on the inner sidewalls of each micro hole. Two metal parts are connected to the resin through the coupling agent. The coupling agent is a thiourea modifier. Under the action of the current in the electrochemical oxidation process, the thiourea modifier is filled in the micro holes and nano holes of the metal parts. The resin is tightly combined with the thiourea modifier, and the metal parts are also tightly combined with the thiourea modifier, so that the resin can be filled in the micro holes and nano holes of the metal parts and combine the two metal parts together. Specifically, it includes the following steps: Step 1, cleaning the metal parts to remove grease on their surfaces; the cleaning process adopts an ultrasonic degreasing process, the ratio of alkaline degreasing agent to water is controlled at 50g / L-80g / L, the water tank temperature is controlled at 55°C-65°C, and the degreasing time is controlled at 1 minute-3 minutes; the main components of the cleaning agent include nonionic surfactants, anionic surfactants, sodium metasilicate pentahydrate and corrosion inhibitors; Step 2: performing sand treatment on the metal parts to form numerous micron-sized holes on their surfaces; the sand treatment is a strong acid chemical corrosion process, the sand temperature is controlled at 40°C-60°C, the ratio of sand solution to water is controlled at 350g / L-450g / L, and the immersion time is controlled at 20 seconds-60 seconds; the sand solution is a mixed aqueous solution of sulfuric acid and hydrochloric acid; Step 3: Deashing the metal parts to preliminarily remove the gray film on the surface; the deashing treatment is a chemical corrosion process, the ratio of nitric acid to water is controlled at 150g / L-250g / L, the ratio of deashing agent to water is controlled at 80g / L-120g / L, the deashing temperature is controlled at 10°C-40°C, and the deashing time is controlled at 1 minute-3 minutes; Step 4: chemically polishing the metal parts to further remove the gray film on the surface; the chemical polishing is a chemical corrosion process using phosphoric acid stock solution, the chemical polishing temperature is controlled at 85°C-95°C, and the chemical polishing time is controlled at 30 seconds-60 seconds; Step 5, oxidizing the metal parts to uniformly form numerous nano-scale holes on the inner side walls of the micron-scale holes, adding thiourea modifiers when the metal parts are oxidized, so that the thiourea modifiers can be fully adsorbed in the micron-scale holes and nano-scale holes under the action of electric current; the oxidation treatment is an electrochemical treatment process, the ratio of phosphoric acid to water in the oxidation solution is controlled at 250g / L-350g / L, the ratio of sulfuric acid to water is controlled at 60g / L-80g / L, the thiourea modifier is added to the oxidation solution, the ratio of the thiourea modifier to the oxidation solution is controlled at 10g-20g / L, the water tank temperature is controlled at 18°C-20°C, the oxidation time is controlled at 15 minutes-20 minutes, and the voltage is controlled at 18V-22V; Step 6: Wash the metal parts with water to remove the acidic substances remaining on the surface; the water washing process uses pure water for cleaning, and the water tank temperature is controlled at 10°C-40°C; Step 7: Dry the metal parts to remove the residual moisture on the surface, and perform in-mold injection molding within 6 hours to avoid excessive volatilization of the thiourea modifier adsorbed in the micron-scale pores and nano-scale pores, so that the resin can completely fill the micron-scale pores and nano-scale pores of the metal parts during in-mold injection molding, thereby forming a metal-resin composite with high airtightness; the drying temperature of the drying treatment is controlled at 70°C-80°C, and the drying time is controlled at 8 minutes-12 minutes.
2. The high airtightness metal-resin composite according to claim 1, characterized in that: The material of the metal component is one of aluminum, aluminum alloy, magnesium alloy, copper alloy, titanium alloy or stainless steel.
3. The high airtightness metal-resin composite according to claim 1, characterized in that: The metal component is a metal upper shell, a metal lower shell, a metal shell, or an independent side strip cut from the shell of the smart electronic product.
4. The high airtightness metal-resin composite according to claim 1, characterized in that: The resin is one or more of PPS, PBT, PA, and PC resins, or a mixture of them with glass fiber, or a mixture of them with carbon fiber.
5. The high airtightness metal-resin composite according to claim 1, characterized in that: In step 2, the diameter of the micron-sized holes is controlled to be 200-400 um.
6. The high airtightness metal-resin composite according to claim 1, characterized in that: In step five, the diameter of the nanoscale pores is controlled to be 30-60 nm.
7. The high airtightness metal-resin composite according to claim 1, characterized in that: The thiourea modified product is a triazine thiourea modified product.
8. The high airtightness metal-resin composite according to claim 1, characterized in that: The deashing treatment is a chemical etching process, and the chemical polishing treatment is a chemical etching process using phosphoric acid stock solution.
Citation Information
Patent Citations
Metal resin complex and process for producing thereof
CN103228418B
Plastic-metal composite and manufacturing method thereof
CN103341945B
High-airtightness metal resin composite
CN210415249U
Insert molding, and manufacturing method therefor
JP2011189631A